On the microphthalmous Lathrobium Gravenhorst species of Turkey III. Two new species from central northern Anatolia, and an updated key to Turkish species (Coleoptera: Staphylinidae: Paederinae) - Anlaş, Si̇nan (Zootaxa, 2022)
In this study, Lathrobium tokatense sp. n. (Tokat province) and L. amasiacum sp. n. (Amasya province), two new microphthalmous species of the genus Lathrobium s. str. from central northern Anatolia, are described and compared to closely related species, L. brignolii Bordoni, L. distortum and L. deforme Assing. Some specimens of the new species were obtained using subterranean pitfall traps in the mesovoid shallow substratum (MSS). The new species are included in an identification key for all microphthalmous Lathrobium s. str. species in Turkey. A total of 10 nominal microphthalmous species are now known to occur in Turkey.